1998
DOI: 10.1083/jcb.140.5.1039
|View full text |Cite
|
Sign up to set email alerts
|

Rab17 Regulates Membrane Trafficking through Apical Recycling Endosomes in Polarized Epithelial Cells

Abstract: A key feature of polarized epithelial cells is the ability to maintain the specific biochemical composition of the apical and basolateral plasma membrane domains while selectively allowing transport of proteins and lipids from one pole to the opposite by transcytosis. The small GTPase, rab17, a member of the rab family of regulators of intracellular transport, is specifically induced during cell polarization in the developing kidney. We here examined its intracellular distribution and function in both nonpolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
119
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(127 citation statements)
references
References 74 publications
(134 reference statements)
7
119
1
Order By: Relevance
“…The corresponding mutation has been found to impair GTP hydrolysis in Ras, Sec4p, Rab11a, and Rab25, thus increasing the amount of GTP-bound form of the protein (Walworth et al, 1992;Frech et al, 1994;. This mutation has been found to have dominantactive effects on the function of a variety of GTPases, with overexpression altering the function of Rab5 , Rab7 (Bucci et al, 2000), Rab8 (Ang et al, 2003), Rab14 (Jununtula et al, 2004), Rab15 (Zuk and Elferink, 1999), and Rab17 (Zacchi et al, 1994).…”
Section: Mutations In the Gtp-binding And Gtp-hydrolysis Domains Altementioning
confidence: 99%
“…The corresponding mutation has been found to impair GTP hydrolysis in Ras, Sec4p, Rab11a, and Rab25, thus increasing the amount of GTP-bound form of the protein (Walworth et al, 1992;Frech et al, 1994;. This mutation has been found to have dominantactive effects on the function of a variety of GTPases, with overexpression altering the function of Rab5 , Rab7 (Bucci et al, 2000), Rab8 (Ang et al, 2003), Rab14 (Jununtula et al, 2004), Rab15 (Zuk and Elferink, 1999), and Rab17 (Zacchi et al, 1994).…”
Section: Mutations In the Gtp-binding And Gtp-hydrolysis Domains Altementioning
confidence: 99%
“…Similar to prototypic ERα target genes, such as MYC and CCND1, RAB17, TPD52L1, and EIF3A could be new candidate genes that promote the growth or migration of ERα-positive breast cancer cells. It is noteworthy that RAB17 is a member of the Rab family of small GTPases and has been shown to be upregulated by knockdown of extracellular signal-regulated kinase (ERK) 2, which is involved in the growth, migration, and invasion of cancer cells [86] . Thus, RAB17 appears to be correlated with a favorable prognosis for ER-positive breast cancer [87] .…”
Section: Identification Of Estrogen-responsive Genes Using Highthrougmentioning
confidence: 99%
“…Brefeldin A disrupts the Golgi apparatus (Lippincott-Schwartz et al, 1990) but also has been reported to interfere with normal sorting and recycling of the holotransferrin bound to its receptor in endocytic vesicles (Xia and Shen, 2001;van Dam and Stoorvogel, 2002). Tyrphostin A8 (AG10) inhibits a GTPase (Rab17) necessary for the fusion of vesicles and endosomes in the apical region of polarized epithelial cells (Lütcke et al, 1993;Hunziker and Peters, 1998;Zacchi et al, 1998;Knight et al, 1995;Hughson and Hopkins, 1990). This is where DMT1 (internalized from the brush border) and apotransferrin (in vesicles coming from the basal region) might come together.…”
Section: Effects On Iron Absorption Of Inhibiting Vesicular Transportmentioning
confidence: 99%